THE DRIVING FACTORS OF EARNINGS MANAGEMENT - Calvin; Dewi Kurnia Indrastuti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
One important part of the company's financial statements is earnings because it provides information to stakeholders about the company's performance. Earnings are used to evaluate management and one of the determinants of the amount of management compensation and to estimate the company's prospects in the future. Earnings management is a practice used by businesses to enhance financial statements over time. The purpose is to attract the attention of users of financial statements to make decisions on investing and granting credit. Therefore, the aim of this study is to determine whether independent commissioners, independent audit committee, audit committee expertise, activity audit committee, size audit committee, leverage, and firm size affect earnings management. This study uses non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period as research objects. The sample selection method used is purposive sampling. The results of this study indicate that leverage and firm size have a positive effect on earnings management. The higher the leverage, the higher the risk of default on the debt owned by the company, among other things because there is an element of uncertainty in business conditions. This is avoided by investors and is a factor that causes the company's management to practice profit management to beautify its financial reports company size has a positive effect on earnings management because large companies will tend to carry out earnings management so that the company is still considered good by investors. While independent commissioners, audit committee size, audit committee independence, audit committee expertise, and audit committee activities have no effect on earnings management.